The existence of weak solutions for a generalized Camassa-Holm equation - Lai, S.; Xie, Q.; Guo, Y.; Wu, Yong Hong (AIMsciences, 2011)
A Camassa-Holm type equation containing nonlinear dissipative effect is investigated. A sufficient condition which guarantees the existence of weak solutions of the equation in lower order Sobolev space H(s) with 1 <= s <= 3/2 is established by using the techniques of the pseudoparabolic regularization and some prior estimates derived from the equation itself.